2002
DOI: 10.1038/sj.ejcn.1601400
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid profiles in Japanese women and men during consumption of walnuts

Abstract: Objective: To determine the serum cholesterol, apolipoproteins and LDL oxidizability in young Japanese women and men during walnut consumption and to evaluate its active principle. Design: Experimental study with a randomized design. Subjects: Twenty healthy women and 20 healthy men. Interventions: Subjects were randomly assigned to consume each of two mixed natural diets for 4 weeks in a cross-over design. Reference and walnut diets were designed and the walnut diet had 12.5% of the energy derived from walnut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 36 publications
5
71
1
Order By: Relevance
“…In addition, specificities in the fatty acid composition of blood or tissue lipid classes make that a given class can be a good biomarker of some PUFA, but not of others. In particular, a-linolenic acid intake is correlated with its percentage in plasma cholesteryl esters (Ma et al, 1995b;Katan et al, 1997;Amiano et al, 2001;Iwamoto et al, 2002), but not with the small amount present in plasma or erythrocyte phospholipids (Ma et al, 1995b;Kobayashi et al, 2001). However, the intake of long-chain n-3 PUFA is mirrored in all blood lipid fractions, especially plasma cholesteryl esters and plasma or red blood cell phospholipids (Ma et al, 1995b;Katan et al, 1997;Kobayashi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, specificities in the fatty acid composition of blood or tissue lipid classes make that a given class can be a good biomarker of some PUFA, but not of others. In particular, a-linolenic acid intake is correlated with its percentage in plasma cholesteryl esters (Ma et al, 1995b;Katan et al, 1997;Amiano et al, 2001;Iwamoto et al, 2002), but not with the small amount present in plasma or erythrocyte phospholipids (Ma et al, 1995b;Kobayashi et al, 2001). However, the intake of long-chain n-3 PUFA is mirrored in all blood lipid fractions, especially plasma cholesteryl esters and plasma or red blood cell phospholipids (Ma et al, 1995b;Katan et al, 1997;Kobayashi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…30 These results provide further evidence that walnut diets are not associated with lipid peroxidation. 6,7 A recent report indicates that, among edible plants, walnuts have one of the highest contents of total antioxidants. 31 Oxidation markers were not worsened by the walnut diet, but neither were they improved; hence, our study does not support the antioxidant potency of walnuts as an alternative explanation for the observed beneficial effects on vascular reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Ros et al (2004) showed that, in moderately hypercholesterolemic patients, walnuts significantly improved oxidative stress-related vascular endothelial function. In a study with a crossover design by Iwamoto et al (2002), forty healthy individuals were randomly assigned to consume a walnut diet (44-58 g/d) or a control diet for 4 weeks. Although plasma lipid levels improved significantly when subjects were fed the walnut diet (i.e.…”
Section: Nut Antioxidants and Human Intervention Studiesmentioning
confidence: 99%